Anti-Radicalism Education for Millenial Generations in Islamic Higher Education - Zamroni Zamroni (STAI Hubbulwathan Duri, 2021)
This study aims to analyse and understand the importance of anti-radicalism education provided to millennial generation students in East Kalimantan. This study uses a qualitative case study approach. The researcher tries to reveal the reality of the meaning in the anti-radicalism education field at three universities in East Kalimantan, including IAIN Samarinda, STIT Balikpapan, and STAI Sangatta East Kutai. The researcher conducted interviews, observations, and documentation to obtain information about the themes studied. Data analysis was carried out circularly, starting with data presentation, data reduction, and concluding. The results show that anti-radicalism education is very much needed in East Kalimantan. Considering that the area has good potential resources, the community is very heterogeneous. The area is used as a hiding place for terrorists, and the anti-radicalism education aims to neutralise the ideas of radicalism that continue to grow.